ARTIFICIAL INTELLIGENCE (AI) USE IN ACADEMIC WRITING FOR EFL/ESL STUDENTS IN HIGHER EDUCATION: A SYSTEMATIC REVIEW - Atya Nur Ramadhanti; Agung Ginanjar Anjaniputra (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2025)
The emergence of Artificial Intelligence (AI) as a large language model (LLM) gives new hopes for addressing challenges faced by higher education students who learn English as Foreign Language (EFL) and Second Language (ESL) in writing scientific papers. However, assuming AI as a new hope in education is imprudent since its advancement could give both challenges and affordances in students’ academic writing. To date, studies that mainly focused on this area are limited, highlighting a need for further exploration. Hence, this study aims to examine to what extent AI could enhance EFL and ESL students in academic writing and its impacts to their writing. Systematic literature review was conducted, following the Preferred Reporting Items for Systematic Reviews and Meta Analysis (PRISMA) 2020 guidelines to synthesize studies over the past year (2023-2025). The findings revealed that AI can significantly assist students particularly in offering personalized feedback, facilitating ideas and content development, as well as providing automated tools. However, it also gives challenges such as plagiarism and disengagement. Therefore, AI integration should be followed by ethical regulations that are updated and dynamics following the fast-moving AI systems and are monitored regularly for its implementation. It is also important to build students’ academic integrity by positioning students’ critical thinking and commitment in academic principles and ethics as a central role in research.